Krytyka militaryzmu i wojny w publicystyce Ludwika Quiddego (1858-1941) - Świątnicka, Iwona (Acta Universitatis Lodziensis. Folia Historica, 1995)
The name of prof. Ludwik Quidde is known as the most eminent defender of peace. He was very active member of peace movement in Germany and in the World. For many years he was the president of German Peace Society and of German Peace of Cartel. However his ideas vere not original. They were rather typical of those days. As many other pacifists, he urged for security, international arbitration and reduction of war expenses. He also wanted to create an international organisation to prevent any futher war. He did not agree to the definition of war in which it was understood as the only way to solve the international affairs. To him this conception was contradictory to the nature of man and the divine rules. He also thought it to be harmful to moral, cultural and economic developmcnt of human civilization. The historie knowledge of prof. L. Quidde influence and shaped his pacifistic publications. With all his strenght he pointed out and criticized all aspects of militarism in Germany. His attilude towards the really possibilities of the world peace movement was realistic. The internal tranquility and the ability to achieve the compromise, also helped him to solve different problems of peace and war.